The relastionship between supply (based on number of Housing unit developed by private sector) and demand (based on population) in Malaysia property market - Mohd, Thuraiya; Alias, Buang (2008)

(untitled)
This is preliminary research which based on secondary data such as Property Market Report, Preliminary Count Report, Malaysian Population Distribution and Demographic Report, Yearbook of Statistic Malaysia and Idaman, the Ministry of Housing and Local Government web site. This initial research is conducted to find the reality of the relationship between supply and demand in residential property market in several townships in Malaysia. The point to ponder in this research is to see whether a neo classical theory which the forces in supply and the law of demand in determining market (Harvey, 1996) is relevant to analyze the property market in the Malaysian context. Does the neo classical theory which indicates that when there is a demand, there must be a supply, is relevant? Does the increasing supply consistent with the increasing demand? The neo classical theory explains that the market will move to an equilibrium level, whereby the level of the quantity of demand is equal to the supply. The theory assumes that the markets are able to function perfectly and the market agents are rational, well informed and constantly strive to maximise their economic well-being. As the result of this preliminaryl study, the research analysis demonstrated that there is a reverse relationship between demand and supply in residential property market, that a supply and a demand may not be directly related. It is not necessary that if there is an increase in demand, there would also be an increase in supply. Thus, the supply is not influence by the demand or vice versa.